(untitled) (Strathmore Law Review, 2017)
Increasingly, states are being called upon to act on illicit financial flows with respect to taxation. In a recent decision, the Court of Appeal of Kenya held that illegal income is taxable under the Kenyan law. There are various arguments for and against taxation of illegal income. As well as arising issues such as deductibility of expenses incurred in the process of income generation, how it relates with the right against self-incrimination and the role of tax law in reinforcing the criminal justice system. This essay is an analysis on whether illegal income in Kenya should be subjected to taxation. The contribution surmises that while taxation of such income may reap benefits, caution must be exercised in order to protect the right against self incrimination.